2018
DOI: 10.17843/rpmesp.2018.353.3683
|View full text |Cite
|
Sign up to set email alerts
|

Infección pulmonar por Lophomonas sp en una paciente con leucemia mieloide aguda

Abstract: Las infecciones por protozoos son prevalentes a nivel mundial, en particular en pacientes inmunosuprimidos. Comunicamos el caso de una paciente procedente de la ciudad de Viña del Mar, Chile, portadora de leucemia mieloide aguda en quien se confirmó una infección por Lophomonas sp. en lavado bronquioalveolar. Se manejó con antibióticos, pero falleció de complicaciones de su enfermedad de base. Existe poca literatura disponible respecto a este microorganismo. Concluimos que debe considerarse a Lophomonas sp. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It indicates that Lophomonas enters the host regardless of the age, the sex, and the immune status. The reviewed publications show that there are new findings in countries like Turkey [ 3 ], Iran [ 10 ], India [ 11 ], and Chile [ 12 ]. Our study has shown that there are also cases in Peru; it may indicate that Lophomonas could be found in any country in it is being identified more frequently [ 2 , 4 , 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicates that Lophomonas enters the host regardless of the age, the sex, and the immune status. The reviewed publications show that there are new findings in countries like Turkey [ 3 ], Iran [ 10 ], India [ 11 ], and Chile [ 12 ]. Our study has shown that there are also cases in Peru; it may indicate that Lophomonas could be found in any country in it is being identified more frequently [ 2 , 4 , 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the case reports, the most common pre-existing condition is immunosuppression (approximately 70% of the patients), other conditions are, patients during the post-transplant periods (approximately, 30%) [ 2 , 10 ] or patients with acute myeloid leukemia (AML) [ 12 ]. In our study 3 of the patients had neoplasia, two had diabetes mellitus and 4 had non-systemic pathologies.…”
Section: Discussionmentioning
confidence: 99%